The mechanisms of the PLS method: an interesting approach for Management research (the impact of Foresight in the strategic management of SMEs) - Abdelkader, Badaoui; Abdelkader, Chettih; Moustafa, Sahi (Dirassat Journal Economic Issue, 2021)
Structural equation modeling based on the PLS method differs from covariance-based methods such as Lisrel by its predictive nature rather than confirmatory and its greater flexibility especially regarding the prerequisites to its use. In addition, it allows addressing the heterogeneity of the data. Thus, it is particularly interesting for researchers in management. After a description of its features and benefits, we propose an illustration based on real data. In addition, the objective of this article is to verify the existence of a Foresight role in the strategic management of SMEs. The study found the significance of the indirect effect of mediation. The inquiry confirmed there is an effect of influence and competitive position as mediators, there is a full mediation of the relationship between the Foresight and Strategic management.